Informação em Saúde no contexto da pandemia: Análise das ações da Secretaria de Estado de Saúde de Minas Gerais entre 2020 e 2021 - Taíssa Pires Maia (2022)
This dissertation aimed to analyze the process of making information available by the State Health Department within the scope of actions and services to promote the fight against the pandemic of COVID-19, during the years of 2020 and 2021. Health information is a right protected by the Brazilian Constitution and by the Law 8080/1990, and in times of outbreaks and diseases such as in the case of the pandemic, it is important to align the content produced and the strategies to ensure health, making it possible for the fellow citizens to meet their informational needs and the organization to take actions accordingly. The dissertation is structured in three theoretical axes: Information Management in Organizations; Health Risk Communication; and Health Information Organization. The methodology of the study addressed the description of the published content, format, and direction, as well as the timeliness and quality of the information produced, given the epidemiological evolution and the health needs of the state of Minas Gerais. An effort was made by the Minas Gerais State Health Department to make information about Covid-19 available in time. The results also point out that a large amount of information made freely available by research centers, governments and companies intensified the need to filter the content produced and effectively distinguish good information from what did not contribute to the scientific and informative debate. The absence of sectorial and strategic management, as well as the lack of training, standardization of organization and formatting of information, made it difficult to access and make the information available. The conclusions suggest the need to institutionalize a culture of continuous monitoring focused on learning and constant communication with the public, which should be intensified in a pandemic environment.